The fire and the rain : agni mattu malé - Karnad, Girish (NewDelhi : Oxford University Press, 2003)
This play by one of India's foremost playwrights and actors is based on a story from the Mahabharata which tellingly illuminates universal themes - alienation, loneliness, love, family, hatred - through the daily lives and concerns of a whole community of individuals.
includes notes.
Keywords: Kannada drama -- Translations into English